Preliminary Phitochemical Analysis Of Guava Leaves (Psidium guajava L.) Extract As Antidiarrheal In Calves - Sudira, I Wayan; Merdana, I Made; Qurani, Suci Nur (Advances in Tropical Biodiversity and Environmental Sciences, 2019)
Guava plants ( Psidium guajava L) are fruit plants originating from South America and can thrive in the territory of Indonesia. Now the biggest center for guava cultivation is spread in DKI Jakarta, West Java, Central Java, East Java, Yogyakarta, Bali, West Nusa Tenggara, Sumatra and Kalimantan. In addition to taking the fruit, guava leaves are also used as a traditional medicine for the treatment of diarrhea in human and animals. This study aims to identify active compounds in guava leaves. That is a secondary  metabolites with pharmacological effects as anti diarrhea such as flavonoid, alkaloid, tannins and essential oils. The leaves sample used in this study were taken from farmers in the West Denpasar area, Bali. Extraction of guava leaf leaves using 96% ethanol, and phytochemical analysis was carried out to detect the presence of active compounds. The data obtained is presented and analyzed descriptively qualitatively. The results showed that the ethanol extract of guava leaves contained active compound inclaude steroid/triterpenoid, phenolics, alkaloids, flavonoids, saponins and tannins. It can be concluded that guava leaf extract contains are potential antidiarrheal